Analyzing the Impact of Global Events on the Indian Stock Market Using Event Study Methodology - Rawat, Dinesh; Rawat, Kalpana (Indian Journal of Research in Capital Markets, 2025)
Purpose : This study aimed to examine the impact of global events such as COVID-19, the Russia–Ukraine war, and the Israel–Palestine war on the Indian stock market. Methodology : The study employed a quantitative research approach, applying the market model event study methodology (ESM), where cumulative abnormal returns (CAR) were calculated for the event window. The data was collected from the National Stock Exchange website. Findings : In the context of COVID-19, the study found that auto, financial services, and metals sectors were negatively affected, while the FMCG, IT, and pharma sectors were positively affected by the COVID-19 event. In the context of the Russia–Ukraine war and the Israel–Palestine war, the study concluded that the auto, financial services, FMCG, and IT sectors benefited, whereas the Russia–Ukraine war and the Israel–Palestine war negatively impacted the metals and pharma sectors. Finally, the findings suggested that the pharma sector was the only sector positively affected by all three events. Practical Implications : This study provided insights into how investor sentiment shifted during global events, enabling market analysts to better predict market reactions to similar future events. Additionally, it helped investors identify sectors that were more sensitive to such global events, aiding in portfolio diversification and risk management. Originality : This study highlighted sector-specific vulnerabilities and opportunities during periods of crisis, which was crucial for both investors and businesses. While much research focused on developed markets such as the United States or Europe, analyzing the response of the Indian stock market to global events offered valuable insights into an emerging market.